2018
DOI: 10.1155/2018/8165476
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Ocular Hypotensive Eyedrops by Ab Interno Trabeculotomy Improves Not Only Ocular Surface Condition But Also Quality of Vision

Abstract: Purpose To investigate the effect of ab interno trabeculotomy using the Trabectome surgical system on tear film stability and functional visual acuity (FVA). Patients and Methods Adult glaucoma patients who underwent Trabectome surgery alone or Trabectome surgery combined with phacoemulsification with intraocular lens insertion were included in this study. Corneal epithelial defects, tear film breakup time (TBUT), tear meniscus height, tear film spreading grade, tear interferometry grade, and FVA were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…This decrease in ocular hypotensive medications serves to reduce the “preservative load” and its deleterious effects on the ocular surface. Eyes treated using ab-interno trabeculotomy have shown improvements in corneal defects, tear spreading, and tear interferometry grades 12…”
Section: Discussionmentioning
confidence: 99%
“…This decrease in ocular hypotensive medications serves to reduce the “preservative load” and its deleterious effects on the ocular surface. Eyes treated using ab-interno trabeculotomy have shown improvements in corneal defects, tear spreading, and tear interferometry grades 12…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of branded eyedropper bottles and generic eyedropper bottles were 37 and 49, respectively. It has been reported that preservatives exert several adverse effects on the ocular surface [1214], even visual function [15]. Some eyedropper bottles attach a filter membrane at the tip to eliminate preservatives from the eye drops.…”
Section: Resultsmentioning
confidence: 99%
“…In the future, we may consider performing trabectome ® surgery for a wide range of indications, from patients with early-stage glaucoma who are receiving single-drug therapy to patients with end-stage glaucoma who cannot undergo trabeculectomy due to advanced age or poor general condition. Kashiwagi et al reported that trabectome ® surgery, both in combined cataract surgery and as a stand-alone procedure, not only lowers IOP but also improves practical vision by improving ocular surface conditions such as corneal epithelial damage due to a decrease in the number of medications [ 14 ]. We believe that this may further contribute to the improvement of patient QOV after surgery.…”
Section: Discussionmentioning
confidence: 99%